Pengaruh Kompetensi, Pengalaman, dan Batasan Waktu terhadap Objektivitas Auditor pada Bpkp Perwakilan Provinsi Papua Barat - Lokananta, Muhammad Ade (Journal of Comprehensive Science, 2025)
This study aims to examine the influence of competence, experience, and time constraints on the objectivity of auditors at the BPKP Representative Office in West Papua Province. This research adopts a quantitative approach. The data used is primary data collected through a questionnaire survey completed by 36 respondents. The data was then analyzed using Structural Equation Modeling (SEM) with the SmartPLS 4.0 analysis tool. The results of this study conclude that competence has a positive effect on auditor objectivity, while experience and time constraints do not affect auditor objectivity.